Same‐sex partnerships in birds: a review of the current literature and a call for more data - Natasha Gillies; Katrina Siddiqi-Davies (Journal of Avian Biology, 2025)
Same‐sex sexual behaviour (SSB), encompassing actions such as courtship, pair bonding, and parenting between individuals of the same sex, has been observed across numerous taxa, including birds. Yet despite its widespread occurrence, SSB remains poorly understood, often dismissed as maladaptive or the result of errors in sex discrimination. However, instances of same‐sex partnerships – persistent pair bonds between same‐sex individuals – challenge these assumptions, particularly in birds, whose diverse mating systems and high level of monogamy imposes strong selective pressures on pair formation and maintenance. This review synthesises our current knowledge of same‐sex partnerships in birds, addressing their evolutionary origins, adaptive benefits, and broader ecological significance. We argue that the prevalence of same‐sex partnerships has likely been underestimated, hindered both by historical biases in interpretation and, especially more recently, logistical challenges in data collection. Drawing on examples from across the avian class, we explore the potential reproductive and social benefits of same‐sex partnerships. By reframing these behaviours as potentially adaptive rather than anomalous, we aim to advance understanding of their evolutionary persistence and encourage more systematic research into their occurrence and implications.